2017
DOI: 10.2147/ott.s140854
|View full text |Cite
|
Sign up to set email alerts
|

Cancer cell dormancy: mechanisms and implications of cancer recurrence and metastasis

Abstract: More recently, disease metastasis and relapse in many cancer patients several years (even some decades) after surgical remission are regarded as tumor dormancy. However, the knowledge of this phenomenon is cripplingly limited. Substantial quantities of reviews have summarized three main potential models that can be put forth to explain such process, including angiogenic dormancy, immunologic dormancy, and cellular dormancy. In this review, newly uncovered mechanisms governing cancer cell dormancy are discussed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(74 citation statements)
references
References 122 publications
(115 reference statements)
0
73
1
Order By: Relevance
“…First, metastasis is an essential hall marker of cancer and always leads to poor survival. [41][42][43] Numerous studies suggested that Tiam1 contributed to invasion and metastasis in various cancers, including osteosarcoma, 44 retinoblastoma, 45 gastric cancer, 46 CRC, [47][48][49][50][51] hepatocellular carcinoma, 25,52 breast cancer, 53 cholangiocarcinoma, 54 cervical cancer, 20 ovarian cancer, 55 nasopharyngeal cancer, 8,16 laryngeal cancer, 56 thyroid carcinoma, 57 nom-small cell lung cancer, 48 pancreatic cancer 6,58,59 and oral squamous cell carcinoma 27 Malliri et al reported that Tiam1 could facilitate E-cadherin-based adhesions between cancer cells in mouse intestinal tumors and human colon tumors, resulting in invasion and metastasis 60 Epithelial-mesenchymal transition (EMT) is a key process of enhancing cancer cell migration, invasion and metastasis. [28][29][30][31] Liu et al reported that Tiam1 overexpression could promote invasiveness and metastasis of thyroid carcinoma in vitro and in vivo by activating Wnt/EMT pathway 57 Similarly, Ding 6 and Yang et al 20 that Tiam1 overexpression could also boost invasion and metastasis of pancreatic cancer and cervical cancer by inducing EMT.…”
Section: Discussionmentioning
confidence: 99%
“…First, metastasis is an essential hall marker of cancer and always leads to poor survival. [41][42][43] Numerous studies suggested that Tiam1 contributed to invasion and metastasis in various cancers, including osteosarcoma, 44 retinoblastoma, 45 gastric cancer, 46 CRC, [47][48][49][50][51] hepatocellular carcinoma, 25,52 breast cancer, 53 cholangiocarcinoma, 54 cervical cancer, 20 ovarian cancer, 55 nasopharyngeal cancer, 8,16 laryngeal cancer, 56 thyroid carcinoma, 57 nom-small cell lung cancer, 48 pancreatic cancer 6,58,59 and oral squamous cell carcinoma 27 Malliri et al reported that Tiam1 could facilitate E-cadherin-based adhesions between cancer cells in mouse intestinal tumors and human colon tumors, resulting in invasion and metastasis 60 Epithelial-mesenchymal transition (EMT) is a key process of enhancing cancer cell migration, invasion and metastasis. [28][29][30][31] Liu et al reported that Tiam1 overexpression could promote invasiveness and metastasis of thyroid carcinoma in vitro and in vivo by activating Wnt/EMT pathway 57 Similarly, Ding 6 and Yang et al 20 that Tiam1 overexpression could also boost invasion and metastasis of pancreatic cancer and cervical cancer by inducing EMT.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the paradox role of pro-and anti-proliferative action of the immune system is shown in tumor evolution [22]. Also, inherent difficulties in detecting and characterizing micrometastatic lesions/individual cells in the patient is another hurdle to assess the relative contribution of various mechanisms of dormancy in the clinical setting [23]. However, the new emerging methodologies, namely microfluidics based on analyzing microliters of serum samples may enable detection of single cells, as wells as DTCs and may aid to capture dormancy dynamics at a single-cell resolution (reviewed in [24][25][26][27]).…”
Section: Introductionmentioning
confidence: 99%
“…Papers published recently have supported the theory that lymph node vessels provide exit routes for metastatic tumor cells to the systemic circulation . From another point of view, it has been shown in clinical studies that tumor cells attached to lung blood vessels are not activated for a considerable period of time, but these dormant tumor cells can be activated by surgical intervention, such as lymph node dissection . In preliminary studies, we have created a mouse model in which dormant tumor cells in lung metastatic lesions are activated after lymph node dissection .…”
Section: Introductionmentioning
confidence: 91%
“…13,14 From another point of view, it has been shown in clinical studies that tumor cells attached to lung blood vessels are not activated for a considerable period of time, but these dormant tumor cells can be activated by surgical intervention, such as lymph node dissection. 15,16 In preliminary studies, we have created a mouse model in which dormant tumor cells in lung metastatic lesions are activated after lymph node dissection. [10][11][12] In this model, the lung metastases were activated after excision of the lymph node into which the tumor cells had been inoculated.…”
Section: Introductionmentioning
confidence: 99%